Historical Analysis of The Role of Dam Bagong for The Economy of The Ngantru Community Trenggalek Regency, 2006-2023 - Lailatul Fitriyah; Ani Zulfatul Rohmah (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
Irrigation is very important for the economic activities of the community, especially rural communities. Irrigation is key in achieving food security because it can help agricultural communities to produce better and more stable harvests so that irrigation has a strategic role in developing an empowered society through agriculture. This article discusses the role of Bagong Dam for the economy of the Ngantru community, Trenggalek Regency. The purpose of this article is to find out and describe the history of Bagong Dam in Trenggalek Regency, the socio-economic conditions of the Ngantru community in Trenggalek Regency, and the role of Bagong Dam for the economy of the Ngantru community in Trenggalek Regency. The writing of this article uses a qualitative research model with a literature study method. Through this method, researchers collected various sources from literature studies relevant to the research topic. The result of the discussion of this article is that Bagong Dam has an influence on the economy of the Ngantru community in Trenggalek Regency. This happens because Bagong Dam functions as an irrigation or water provider for the agricultural areas of the Ngantru community so that with the fulfilment of water from Bagong Dam, agriculture is able to produce quality and abundant rice. As a result, this will also affect the economy of the Ngantru community for the better.